Current Activities of the Coalition of Cancer Cooperative Groups. (13th December 2018) - Bertagnolli, Monica M; Blaney, Susan M; Blanke, Charles D; Curran, Walter J; Dancey, Janet; Mannel, Robert S; O'Dwyer, Peter J; Schnall, Mitchell D; Wolmark, Norman; ,
Abstract: The Coalition of Cancer Cooperative Groups is an organization representing the interests of patients and researchers who conduct research through the National Cancer Institute-supported National Clinical Trials Network (NCTN). The NCTN provides a crucial mechanism for executing practice-changing cancer clinical research to achieve both cancer control and development of new therapeutic agents or modality approaches. Public funding, largely through the National Cancer Institute, ensures that the work of the NCTN achieves important research that would not otherwise be accomplished in the private sector. In fall 2017, the Coalition of Cancer Cooperative Groups convened a Scientific Leadership Council to review the current state of the network with regard to research capabilities and to develop a list of research questions to be prioritized by the network. This report presents the results of this meeting, detailing a roadmap for future work by the NCTN.